The effect of cork-stripping damage on diameter growth of Quercus suber L. - Costa, A.; Pereira, H.; Oliveira, A. (Forestry, 2004)
The Mediterranean cork oak (Quercus suber L.) agro-forestry system is oriented towards cork production, with cork being extracted from tree stem and branches as planks by cutting with an axe and stripping off. The effect of damage to the tree during cork stripping was studied in cork oaks, weakened by wounding, by following the diameter growth and its seasonality during a 9-year production cycle, and comparing them with healthy cork oaks. Tree wounding decreased diameter growth during the following cycle, e.g. 8.5 mm a−1 and 9.8 mm a−1 for weakened and healthy trees, respectively, mostly in the 2 years immediately following the cork stripping. The beginning of annual growth in spring and the occurrence of the highest increments in June–August were delayed by about 1 month in the weakened trees. The cork produced by weakened trees was reduced by 13 per cent in thickness, with average cork ring widths of 3.3 mm a−1 vs. 3.8 mm a−1 for healthy trees.
10.1093/forestry/77.1.110.1093/forestry/77.1.1
Keywords: Cork Production; stripping; wound responses (PG)

The effect of cork-stripping damage on diameter growth of Quercus suber L. - Costa, a; Pereira, H; Oliveira, A (Forestry, 2004)
The Mediterranean cork oak (Quercus suber L.) agro-forestry system is oriented towards cork production, with cork being extracted from tree stem and branches as planks by cutting with an axe and stripping off. The effect of damage to the tree during cork stripping was studied in cork oaks, weakened by wounding, by following the diameter growth and its seasonality during a 9-year production cycle, and comparing them with healthy cork oaks. Tree wounding decreased diameter growth during the following cycle, e.g. 8.5 mm a−1 and 9.8 mm a−1 for weakened and healthy trees, respectively, mostly in the 2 years immediately following the cork stripping. The beginning of annual growth in spring and the occurrence of the highest increments in June–August were delayed by about 1 month in the weakened trees. The cork produced by weakened trees was reduced by 13 per cent in thickness, with average cork ring widths of 3.3 mm a−1 vs. 3.8 mm a−1 for healthy trees.
10.1093/forestry/77.1.1
Keywords: Cork Production; stripping; wound responses (PG)

The effect of cork-stripping damage on diameter growth of Quercus suber L. - Costa, a; Pereira, H; Oliveira, A (Forestry, 2004)
The Mediterranean cork oak (Quercus suber L.) agro-forestry system is oriented towards cork production, with cork being extracted from tree stem and branches as planks by cutting with an axe and stripping off. The effect of damage to the tree during cork stripping was studied in cork oaks, weakened by wounding, by following the diameter growth and its seasonality during a 9-year production cycle, and comparing them with healthy cork oaks. Tree wounding decreased diameter growth during the following cycle, e.g. 8.5 mm a−1 and 9.8 mm a−1 for weakened and healthy trees, respectively, mostly in the 2 years immediately following the cork stripping. The beginning of annual growth in spring and the occurrence of the highest increments in June–August were delayed by about 1 month in the weakened trees. The cork produced by weakened trees was reduced by 13 per cent in thickness, with average cork ring widths of 3.3 mm a−1 vs. 3.8 mm a−1 for healthy trees.
10.1093/forestry/77.1.1
Keywords: Cork Production; stripping; wound responses (PG)

Variation in cork production of the cork oak between two consecutive cork harvests - Costa, a; Oliveira, A C (Forestry, 2001)
The variation in the cork produced by individual trees (Quercus suber L.) in three distinct locations, Mora, Alcácer do Sal and Benavente, is characterized by measurements made during two consecutive harvests of cork in the same trees. Particular emphasis is given to the variability in the weight of cork produced by individual trees and its mean caliper for the two strippings in each region. A good linear correlation between the tree circumference after the first stripping and the weight of the cork produced 9 years later as well as a poor linear correlation between the first variable and the caliper of the cork produced 9 years later is reported. A cork oak diameter curve is presented for each region, considering their two radial growths: the wood growth, which is cumulative, and the cork growth, which is the 9‐year growth.
10.1093/forestry/74.4.337
Keywords: Cork Production; Growth (PG); stripping; variability

Variation in cork production of the cork oak between two consecutive cork harvests - Costa, A.; Oliveira, A. C. (Forestry, 2001)
The variation in the cork produced by individual trees (Quercus suber L.) in three distinct locations, Mora, Alcácer do Sal and Benavente, is characterized by measurements made during two consecutive harvests of cork in the same trees. Particular emphasis is given to the variability in the weight of cork produced by individual trees and its mean caliper for the two strippings in each region. A good linear correlation between the tree circumference after the first stripping and the weight of the cork produced 9 years later as well as a poor linear correlation between the first variable and the caliper of the cork produced 9 years later is reported. A cork oak diameter curve is presented for each region, considering their two radial growths: the wood growth, which is cumulative, and the cork growth, which is the 9‐year growth.
10.1093/forestry/74.4.33710.1093/forestry/74.4.337
Keywords: Cork Production; Growth (PG); stripping; variability

The cork oak tree in California - Metcalf, Woodbridge (Economic Botany, 1947)
Cork oaks have been planted in Cali- fornia since about 1855, and there are some outstandingly fine specimen trees growing from San Diego to Eureka at elevations below 2,700 feet. There are about 5,000 trees more than ten years old in the state. Cork oak acorns produced in Cali- fornia average 70 per pound, have a high germinative capacity which can be main- tained for twelve months or more by moist cold storage at 38° F., and during most years it should be possible to obtain from five to ten tons of cork oak acorns from California trees. During the past six years about 200,- 000 seedling trees of cork oak have been grown and distributed to land owners under the cooperative cork oak project. Where carefully planted, protected from animal damage and given adequate irri- gation, shade and care, many of these plantations have shown excellent sur- vival and growth. Because of the kind interest and co- operation on the part of owners of cork oak trees, it has been possible to carry on experimental stripping of about 500 cork oaks during the past six years. The stripping season has been found to be from about July 1 to early in October. Most vigorous and full-crowned trees can be stripped easily with the special tools developed and with virtually no damage to the inner bark. It is not advisable to strip trees which are thin crowned or suffering from drought, insects or dis- ease. Removal of cork from ornamental cork oaks changes their appearance but does not seriously check their growth or lessen their ornamental character. The 15 tons of cork has been quite thoroughly tested and found to be well suited for the making of composition cork articles, insulation blocks and other been rapid and satisfactory with trees, usually regaining the diameter before stripping in five years. Indications are that the reproduction cork is of excellent quality. Trees 25 to 30 years of age when stripped have put on a growth of 100 pounds of reproduction cork in five years. The most serious insect enemy of the cork oak in California is the gall wasp which kills many twigs, particularly on trees in dry locations. There is no known control for this pest. If the cooperative distribution of trees can be continued until there are one mil- lion cork oaks growing in California, they will when 30 years old contain an emergency supply of 50,000 tons of cork. This amount may be increased and the quality improved by successive stripping of the trees after they become 20 years of age.
Keywords: acorns; California; Cork; cork oak trees; diameter; growth (voyant); stripping